PENGARUH SIKLUS OPERASIONAL, RESIKO HUTANG DAN UKURAN PERUSAHAAN TERHADAP PERSISTENSI LABA - Piter Nainggolan (POLITEKNIK LP3I JAKARTA, 2021)
The purpose of this study was to examine the effect of operating cash flow, debt levels, and firm size on earnings persistence. Earnings persistence reflects the quality of a company's earnings, which indicates that the company can maintain profit in its activities. This study used secondary data and the research sample is determined by purposive sampling method. The sample which used in this study were 8 retail goods companies listed on the Indonesia Stock Exchange (BEI) for the period of 2016 until 2019. The analysis in this study used the SPSS 25 program where the statistical model used was multiple regression analysis.Based on the research results, the conclusion obtained is that the level of company’s debt and company’s size partially has no effect on earnings persistence. Operating cashflow partially affects earnings persistence.Keywords: Background of the board of commissioners, citizenship of the board of commissioners, independent board of commissioners, audit committee